Bacterial extracellular vesicles in the initiation, progression and treatment of atherosclerosis - Yuling Lin; Jingyu Wang; Fan Bu; Ruyi Zhang; Junhui Wang; Yubing Wang; Mei Huang; Yiyi Huang; Lei Zheng; Qian Wang; Xiumei Hu (Gut Microbes)
Atherosclerosis is the primary cause of cardiovascular and cerebrovascular diseases. However, current anti-atherosclerosis drugs have shown conflicting therapeutic outcomes, thereby spurring the search for novel and effective treatments. Recent research indicates the crucial involvement of oral and gastrointestinal microbiota in atherosclerosis. While gut microbiota metabolites, such as choline derivatives, have been extensively studied and reviewed, emerging evidence suggests that bacterial extracellular vesicles (BEVs), which are membrane-derived lipid bilayers secreted by bacteria, also play a significant role in this process. However, the role of BEVs in host-microbiota interactions remains insufficiently explored. This review aims to elucidate the complex communication mediated by BEVs along the gut-heart axis. In this review, we summarize current knowledge on BEVs, with a specific focus on how pathogen-derived BEVs contribute to the promotion of atherosclerosis, as well as how BEVs from gut symbionts and probiotics may mitigate its progression. We also explore the potential and challenges associated with engineered BEVs in the prevention and treatment of atherosclerosis. Finally, we discuss the benefits and challenges of using BEVs in atherosclerosis diagnosis and treatment, and propose future research directions to address these issues.